Pengaruh adopsi Technology Acceptance Model terhadap layanan virtual buka rekening BSI - Ivena Defira Selly Aryanti; Mutia Aressandy Aressandy; Fuad Hasyim (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2023)
The purpose of this research is to analyze the influence of the TAM constructs, which consist of usefulness, ease of use, and security, on the virtual account opening service of BSI in Kartasura District. The population in this study is the community in Kartasura District. The sample was obtained using a nonprobability sampling technique by distributing questionnaires, resulting in 100 respondents. The data analysis technique used multiple linear regression with SPSS. The results showed that the variables of usefulness, ease of use, and security had a significant partial and simultaneous effect on the usage decision.